(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Maxillofacial reconstruction surgery has largely depend on on local flaps for soft tissue reconstruction and nonvascularized bone grafts for bony reconstruction. The paradigm shift has been to vascularized free tissue for larger soft tissue, bone, or composite defects in the head and neck and biologic agents such as bone morphogenic proteins (BMP), blood components such as platelet-rich plasma and fibrin, and tissue engineering. Although osseous-free flaps are acknowledged as a superior reconstructive option, there are a number of different flaps – iliac crest, fibula, scapula or radial forearm. Each of these has benefits and disadvantages for the reconstruction, with success defined by flap survival, donor site morbidity, capacity for normal speech, ethetics, oral competence and diet and successful dental rehabilitation. The osteocutaneous radial flap is reliable, and relatively simple to harvest, which will ensure that it remains one of the established reconstructive options in most maxillofacial units. The introduction of prophylactic internal fixation augments the role of the osteocutaneous radial flap for repair of defects that require a relatively small volume of bone and an appreciable area of thin soft tissue, specially when a long vascular pedicle is desirable. This includes low level defects of the maxilla, some defects of the mandible, and niche reconstructions, such as the orbital rim. the focus of this review are different surgical techniques, indications and outcomes of osteocutaneous radial forearm free flap in Maxillofacial reconstruction.